Can birth weight predict offspring’s lung function in adult age? Evidence from two Swedish birth cohorts - Aleksandra Sakic; Magnus Ekström; Shantanu Sharma; Peter M. Nilsson (Respiratory Research, 2022)
Abstract Background Associations between birth weight (BW) and adult lung function have been inconsistent and limited to early adulthood. We aimed to study this association in two population-based cohorts and explore if BW, adjusted for gestational age, predicts adult lung function. We also tested adult lung function impairment according to the mis-match hypothesis—small babies growing big as adults. Methods We included 3495 individuals (aged 46.4 ± 5.4 years) from the Malmo Preventive Project (MPP), Sweden, born between 1921 and 1949, and 1401 young to middle-aged individuals (aged 28.6 ± 6.7 years) from the Malmo Offspring Study (MOS) with complete data on BW and gestational age. Adult lung function (forced vital capacity [FVC], forced expiratory volume in one second [FEV1] and the FEV1/FVC-ratio) were analysed as level of impairment (z-score), using multiple linear and logistic regressions. Results BW (z-score) did not predict adult lung function in MPP, whereas BW was a significant (p = 0.003) predictor of FEV1 following full adjustment in MOS. For every additional unit increase in BW, children were 0.77 (95% CI 0.65–0.92) times less likely to have impaired adult lung function (FEV1). Moreover, adults born with lower BW (< 3510 g) showed improved lung function (FEV1 and FEV1/FVC in MOS and MPP, respectively) if they achieved higher adult body weight. Conclusions Adults born with lower birth weight, adjusted for gestational age, are more likely to have impaired lung function, seen in a younger birth cohort. Postnatal growth pattern may, however, compensate for low birth weight and contribute to better adult lung function.